Atherogenic index of plasma and left ventricular ejection fraction in newly diagnosed type 2 diabetes mellitus patients - Shaikat Mondal (Wolters Kluwer Medknow Publications, 2021)
Background: Atherogenic index of plasma (AIP), a logarithm of ratio of triglycerides and high-density lipoprotein-cholesterol is associated with the risk of cardiovascular diseases. The cardiovascular complication in Type 2 diabetes is often assessed by the left ventricular ejection fraction (LVEF). Aim: This study aimed to observe and to find any correlation between LVEF and AIP in newly diagnosed Type 2 diabetes mellitus patients. Materials and Methods: In this cross-sectional observational study, we recruited 140 (male 81, female 59) newly diagnosed Type 2 diabetes mellitus patients from a tertiary care hospital. Plasma lipids were measured from venous blood after 12-h fasting. The LVEF was measured by echocardiography. Data were presented as mean, standard deviation, and statistically tested by Chi-square and Pearson correlation coefficient in IBM SPSS Statistics 20. Results: The mean age of the participants was 53.95 ± 11.63 years (male 53.85 ± 11.12 years, female 54.08 ± 12.39 years, unpaired t-test P = 0.91). The mean LVEF was 0.59 ± 0.06 and 0.6 ± 0.05 (unpaired t-test P = 0.17) in males and females, respectively. The AIP was 0.57 ± 0.07 and 0.57 ± 0.07 (unpaired t-test P = 0.97) in males and females, respectively. There was a negative correlation (r = −0.56, P < 0.001) between LVEF and AIP. Conclusion: Newly diagnosed type 2 diabetes mellitus patients showed a high AIP. Hence, serum lipid profile may be tested early in these patients. Patients with a higher AIP may have lower LVEF. Hence, diabetic patients with a high AIP may be screened for LVEF periodically for early detection and management of heart failure.